1994
DOI: 10.1007/bf00185843
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical identification of programmed cell death in the fusing fetal mouse palate by specific labelling of DNA fragmentation

Abstract: The process of palate fusion was examined in 13- and 14-day-old mouse fetuses by using in situ staining for nuclear DNA fragmentation (TUNEL method) and immunofluorescent staining for keratin, with special reference to the disruption of the midline epithelial seam. TUNEL-positive cells were found in the disappearing midline seam and the oral and nasal epithelial triangles at some late stages of palate fusion, but not in the palatal shelves prior to contact or in the intact midline epithelial seam. It seems tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 31 publications
3
86
0
1
Order By: Relevance
“…In contrast to the few studies of the lip fusion process, the fate of the medial edge epithelial (MEE) cells of the secondary palatal shelves, which form the midline epithelial seam upon palatal shelf adhesion, has been studied extensively although considerable disagreement still exists. TEM and cell biological studies have provided clear evidence of apoptosis of at least a portion of the MEE cells (Glucksmann, 1965;Saunders, 1966;DeAngelis and Nalbandian, 1968;Smiley and Dixon, 1968;Shapiro and Sweney, 1969;Smiley and Koch, 1975;Mori et al, 1994;Taniguchi et al, 1995;Cuervo et al, 2002;Cuervo and Covarrubias, 2004). Others, however, reported that the midline epithelial seam cells looked healthy at the TEM level and found evidence of transdifferentiation of MEE cells into mesenchymal cells by using various cell labeling techniques (Fitchett and Hay, 1989;Shuler et al, 1991Shuler et al, , 1992Griffith and Hay, 1992;Sun et al, 1998;Martinez-Alvarez et al, 2000;Nawshad et al, 2004).…”
Section: Is Programmed Cell Death Emt or Both The Mechanism Involvementioning
confidence: 99%
“…In contrast to the few studies of the lip fusion process, the fate of the medial edge epithelial (MEE) cells of the secondary palatal shelves, which form the midline epithelial seam upon palatal shelf adhesion, has been studied extensively although considerable disagreement still exists. TEM and cell biological studies have provided clear evidence of apoptosis of at least a portion of the MEE cells (Glucksmann, 1965;Saunders, 1966;DeAngelis and Nalbandian, 1968;Smiley and Dixon, 1968;Shapiro and Sweney, 1969;Smiley and Koch, 1975;Mori et al, 1994;Taniguchi et al, 1995;Cuervo et al, 2002;Cuervo and Covarrubias, 2004). Others, however, reported that the midline epithelial seam cells looked healthy at the TEM level and found evidence of transdifferentiation of MEE cells into mesenchymal cells by using various cell labeling techniques (Fitchett and Hay, 1989;Shuler et al, 1991Shuler et al, , 1992Griffith and Hay, 1992;Sun et al, 1998;Martinez-Alvarez et al, 2000;Nawshad et al, 2004).…”
Section: Is Programmed Cell Death Emt or Both The Mechanism Involvementioning
confidence: 99%
“…Cytological changes indicative of cell death such as ultrastructural changes of cell organelles, cessation of DNA synthesis and increased lysosomal levels have been observed in MEE cells prior to the contact of palatal shelves (Shapiro and Sweney, 1969;Smiley, 1970;Hudson and Shapiro, 1973;Greene and Pratt, 1976). On the other hand, using in situ labeling of DNA fragmentation, we previously detected a cytochemical evidence for apoptotic cell death occurring in the disappearing midline epithelial seam at some late stage of palatal fusion when the midline epithelial seam was disrupting, but not at earlier stages of palatogenesis (Mori et al, 1994). Recently Cuervo et al (2002) claimed that the contact of palatal shelves is necessary for cell death activation in MEE and that cell death is a primary process required for palatal fusion.…”
Section: Introductionmentioning
confidence: 99%
“…As palatal fusion proceeds, the MEE seam quickly breaks down and ultimately the epithelial cells disappear from the midline (Shuler, 1995). It has been demonstrated that there are three distinct fates for MEE, which include epithelial-mesenchymal transformation (Shuler et al, 1991(Shuler et al, , 1992Griffith and Hay, 1992;Martinez-Á lvarez et al, 2000), migration (Carette and Ferguson, 1992), and programmed cell death (Mori et al, 1994;Martinez-Á lvarez et al, 2000). Despite these three different fates, the MEE cells all share a common feature, they cease DNA synthesis (Gehris and Greene, 1992) before the initial formation of the midline epithelial seam.…”
Section: Introductionmentioning
confidence: 99%